The Association Between the Extent of Glioblastoma Resection and Survival in Light of MGMT Promoter Methylation in 326 Patients With Newly Diagnosed IDH-Wildtype Glioblastoma - Incekara, Fatih; Smits, Marion; van der Voort, Sebastian R.; Dubbink, Hendrik Jan; Atmodimedjo, Peggy N.; Kros, Johan M.; Vincent, Arnaud J. P. E.; van den Bent, Martin (Frontiers in Oncology, 2020)
Background The association between contrast enhanced (CE) and non-contrast enhanced (NCE) tumor resection and survival in patients with glioblastoma in relation to molecular subtypes is poorly understood. The aim of this study was to assess the association between CE and NCE tumor resection and survival in light of MGMT promoter methylation in newly diagnosed IDH-wildtype glioblastoma. Materials and Methods Patients with newly diagnosed IDH-wildtype glioblastoma who underwent surgery were eligible. CE and NCE tumor volumes were assessed on pre- and post-operative MRI scans and extent of resection was calculated. The association between CE and NCE tumor resection and survival was evaluated using multivariable Cox proportional hazards models and Kaplan Meier estimates. Results 326 patients were included: 177 (54.3%) with and 149 (45.7%) without MGMT methylation. Multivariable Cox proportional hazards models stratified for MGMT methylation identified age ≤ 65y (HR 0.63; 95% CI, 0.49-0.81; p < 0.0001), chemoradiation (HR 0.13; 95% CI, 0.09-0.19; p < 0.0001), maximal CE tumor resection (HR 0.58; 95% CI, 0.39-0.87; p = 0.009), extended NCE tumor resection (HR 0.71; 95% CI, 0.53-0.93; p = 0.014) and minimal residual CE tumor volume (HR 0.64; 95% CI, 0.46-0.88 p = 0.007) as being associated with longer overall survival. Kaplan Meier estimates showed that extensive surgery was more beneficial for patients with MGMT methylated glioblastoma. Conclusions This study shows an association between maximal CE tumor resection, extended NCE tumor resection, minimal residual CE tumor volume and longer overall survival in patients with newly diagnosed IDH wildtype glioblastoma. Intraoperative imaging and stimulation mapping may be used to pursue safe and maximal resection.